Oil Sparks in the Amazon Local Conflicts, Indigenous Populations, and Natural Resources - Vasquez, Patricia I.; Project Muse; Project Muse. (Project Muse, 2013)
For decades, studies of oil-related conflicts have focused on the effects of natural resource mismanagement, resulting in great economic booms and busts or violence as rebels fight ruling governments over their regions' hydrocarbon resources. In Oil Sparks in the Amazon, Patricia I. Vasquez writes that while oil busts and civil wars are common, the tension over oil in the Amazon has played out differently, in a way inextricable from the region itself. Oil disputes in the Amazon primarily involve local indigenous populations. These groups' social and cultural identities differ from the rest of the population, and the diverse disputes over land, displacement, water contamination, jobs, and wealth distribution reflect those differences. Vasquez spent fifteen years traveling to the oil producing regions of Latin America, conducting hundreds of interviews with the stakeholders in local conflicts. She analyzes fifty-five social and environmental clashes related to oil and gas extraction in the Andean countries (Peru, Ecuador, and Colombia). She also examines what triggers local hydrocarbons disputes and offers policy recommendations to resolve or prevent them. Vasquez argues that each case should be analyzed with attention to its specific sociopolitical and economic context. She shows how the key to preventing disputes that lead to local conflicts is to address structural flaws (such as poor governance and inadequate legal systems) and nonstructural flaws (such as stakeholders' attitudes and behavior) at the outset. Doing this will require more than strong political commitments to ensure the equitable distribution of oil and gas revenues. It will require attention to the local values and culture as well.
List of illustrations -- Preface -- Introduction -- Tracing oil- and gas- related conflicts -- Indigenous peoples and natural resource development -- Structural causes of local conflicts -- Transient triggers of local conflicts -- Conclusion -- Notes -- Bibliography -- Index.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages [151]-167) and index.
Description based on print version record.
Keywords: Social conflict -- South America; Indians of South America -- Social conditions; Petroleum industry and trade -- Environmental aspects -- South America; Petroleum industry and trade -- Social aspects -- South America; Electronic books; Electronic books